2017
DOI: 10.4172/2572-0791.1000125
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunctions in Depression

Abstract: Sexual dysfunction is one of the common symptoms seen in depression. Presentations include decreased libido, erectile dysfunction, arousal difficulties and orgasm related dysfunctions. The probable causes of sexual dysfunction in such patients are complex and biological, psychological as well as psychosocial factors are likely to play an important role. Sexual dysfunction could also occur as an adverse effect of anti-depressants although it is difficult to establish whether the dysfunction is due to the illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Keywords with a negative polarity, such as bad, die or pain, seem to be pervasive in the speech of depressed individuals as confirmed in our study. Finally, the reduced sexual drive is a well-known indication of depression (Manohar et al, 2017), therefore, it is to be expected that depressed individuals tend to use fewer words with sexual connotation as confirmed in our study.…”
Section: Self-reported Signs Of Depressionsupporting
confidence: 83%
“…Keywords with a negative polarity, such as bad, die or pain, seem to be pervasive in the speech of depressed individuals as confirmed in our study. Finally, the reduced sexual drive is a well-known indication of depression (Manohar et al, 2017), therefore, it is to be expected that depressed individuals tend to use fewer words with sexual connotation as confirmed in our study.…”
Section: Self-reported Signs Of Depressionsupporting
confidence: 83%
“…We specifically evaluated the presence of depression (by PHQ9) 15 at baseline as it can be a cause of sexual dysfunction. 16,17 Its treatment often leads to restoration of sexual functioning, although antidepressants may themselves also be associated to sexual disabilities. 17 At baseline, the prevalence of major depression in our cohort was in line with previous reports in HCV-patients 1,18 (20.4%).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Its treatment often leads to restoration of sexual functioning, although antidepressants may themselves also be associated to sexual disabilities. 17 At baseline, the prevalence of major depression in our cohort was in line with previous reports in HCV-patients 1,18 (20.4%). We have shown that assessment of depression is important when exploring sexuality: major depression (PHQ9 > 10) (but not the use of antidepressants) and age ≥ 55 years were independently associated with sexual dysfunction at baseline, with prevalence close to 90% in this subpopulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations